Antivitamin B12 Inhibition of the Human B12‐Processing Enzyme CblC: Crystal Structure of an Inactive Ternary Complex with Glutathione as the Cosubstrate. Issue 26 (23rd May 2017) - Ruetz, Markus; Shanmuganathan, Aranganathan; Gherasim, Carmen; Karasik, Agnes; Salchner, Robert; Kieninger, Christoph; Wurst, Klaus; Banerjee, Ruma; Koutmos, Markos; Kräutler, Bernhard
Abstract: B12 antivitamins are important and robust tools for investigating the biological roles of vitamin B12 . Here, the potential antivitamin B12 2, 4‐difluorophenylethynylcobalamin (F2PhEtyCbl) was prepared, and its 3D structure was studied in solution and in the crystal. Chemically inert F2PhEtyCbl resisted thermolysis of its Co−C bond at 100 °C, was stable in bright daylight, and also remained intact upon prolonged storage in aqueous solution at room temperature. It binds to the human B12 ‐processing enzyme CblC with high affinity ( K D =130 nm ) in the presence of the cosubstrate glutathione (GSH). F2PhEtyCbl withstood tailoring by CblC, and it also stabilized the ternary complex with GSH. The crystal structure of this inactivated assembly provides first insight into the binding interactions between an antivitamin B12 and CblC, as well as into the organization of GSH and a base‐off cobalamin in the active site of this enzyme. Abstract : Antivitamins in action : A new, chemically robust antivitamin B12 was used for biochemical analysis of the inhibition of CblC, the key B12 ‐processing enzyme of humans. The crystal structure of the inactive enzyme complex provides detailed insight into CblC loaded with a cobalamin and its cosubstrate glutathione.